Color change kinetics of okra undergoing microwave drying - Dadali, Gokce; Apar, Dilek Kilic; Ozbek, Belma (TAYLOR & FRANCIS INC, 2007)
In this present study, the effect of microwave output power and sample amount on color change kinetics of Turkey okra (Hihiscus esculenta L.) were investigated by using microwave drying technique. The color parameters for the color change of the materials were quantified by Hunter L (whiteness/darkness), a (redness/greenness), and b (yellowness/blueness) values. These values were also used for calculation of the total color change (Delta E), chroma, hue angle and browning index. The microwave drying process changed color parameters of L, a, and h, causing a color shift toward the darker region. The values of L and b decreased, whereas values of a and total color change (Delta E) increased during microwave drying. The mathematical modeling study of color change kinetics showed that L and b fit a first-order kinetic model, whereas a and total color change (Delta E) followed a zero-order kinetic model. However, chroma and browning index (BI) followed a first-order kinetic model, whereas hue angle followed a zero-order kinetic model. On the other hand, the data of the total color change (Delta E), chroma, hue angle, and browning index depending on the ratio of the microwave output power to sample amount were adequately fitted to a quadratic model. For calculation of the activation energy for color change kinetics parameters, the exponential expression based on Arrhenius equation was used.
Keywords: color change kinetics; microwave drying; okra; DEGRADATION KINETICS; GREEN COLOR; GRAPE JUICE; QUALITY; PUREE; Engineering